2016
DOI: 10.1177/0954411915617983
|View full text |Cite
|
Sign up to set email alerts
|

Foot–ankle simulators: A tool to advance biomechanical understanding of a complex anatomical structure

Abstract: In vitro gait simulations have been available to researchers for more than two decades and have become an invaluable tool for understanding fundamental foot-ankle biomechanics. This has been realised through several incremental technological and methodological developments, such as the actuation of muscle tendons, the increase in controlled degrees of freedom and the use of advanced control schemes. Furthermore, in vitro experimentation enabled performing highly repeatable and controllable simulations of gait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Thus, people usually perform a variaety of activities with one or other limb in a daily basis [1,4,5,6]. This "unconscious training" helps to develop abilities that can make a difference when performing Activities of Daily Living.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, people usually perform a variaety of activities with one or other limb in a daily basis [1,4,5,6]. This "unconscious training" helps to develop abilities that can make a difference when performing Activities of Daily Living.…”
Section: Introductionmentioning
confidence: 98%
“…It has been observed that for a right dominat subject is easier to perform such movements (flexion/extension, supination/pronation, aduction/abduction), in clockwise direction whereas for the left-dominant subject is easier to perform the movements in anti-clockwise direction. Therefore a proposed protocol must include both feet and both directions (clockwise and anti-clockwise) [1,4,7,8] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are well protected and have only minor tendon attachments and are not subjected to strong pulling forces. Near the head of the first metatarsal, on the plantar surface of the foot, are two seamed bones (a small, oval-shaped bone which develops inside a tendon, where the tendon passes over a bony prominence) they are held in place by tendons, and ligaments [11] ( Figure 1). …”
Section: Structure Of Footmentioning
confidence: 99%